Analysis of the Village Government Work Plan Implementation (RKPDes) Fiscal Year 2022 Gonggang Village, Poncol Sub-District, Magetan Regency - Vani Rizka Fatmala; Ach. Apriyanto Romadhan; Iradhad Taqwa Sihidi (Jurnal Public Policy, 2023)
The Village Government Work Plan (RKPDes) is the only one guidline for implementation of the development government at the village level within a period of one year. Juridically, the village government itself is stated in the Village Law (UU Desa) Number 6 of 2014. In this journal article, researchers are trying to conduct an analytical study with a focus on studies related to the implementation of the Village Government Work Plan (RKPDes) 2022 in Gonggang Village, Poncol District, Magetan Regency more specifically from the perspective of the village government's steps in maximizing the development of existing potentials in Gonggang Village. Therefore, this study aims to answer the main research problem; How the process of preparing, implementing and reporting for RKPDes 2022 in Gonggang Village? What are the factors that affect the running of RKPDes 2022 in Gonggang Village?. The research method used is a qualitative method with a descriptive approach. The source of the research data was obtained from documents belonging to Gonggang Village, the results of interviews and observations. In order to strengthen the research, interviews were conducted with four interviewees, consisting of the Gonggang Village Consultative Body (BPD), Gonggang Village Head, Gonggang Village Secretary and Gonggang Village Treasurer. The results showed that the mechanism for implementing RKPDes 2022 in Gonggang Village has been running quite well, but there are still shortcomings and not optimal because there are activity programs that have not been implemented in 2022 due to funding constraints.